2017
DOI: 10.1162/rest_a_00634
|View full text |Cite
|
Sign up to set email alerts
|

A More Timely House Price Index

Abstract: Using listings data, we construct a new repeat-sales house price index that describes house values at the contract date when the price is determined rather than the closing date when the property is transferred. We show that this difference in timing helps explain several puzzles about house prices, including their strong short-term serial correlation and their weak correlation with stock prices and macroeconomic news shocks. In addition, we show that a variant of our index that relies exclusively on listings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…The authors concluded that prices/values obtained at different stages of the selling process are comparable only if the qualitative and quantitative characteristics of flats are considered, making them useful for building price indexes. In another study, Anenberg and Laufer (2017) came to interesting conclusions. Using the information on two million offers from the nine largest U.S. cities in the years 2008-2012, the authors showed that the asking price-based index accurately forecasts the Case-Shiller index (based on the repeat sales method and asking prices) with a few-month lead.…”
Section: Datamentioning
confidence: 89%
“…The authors concluded that prices/values obtained at different stages of the selling process are comparable only if the qualitative and quantitative characteristics of flats are considered, making them useful for building price indexes. In another study, Anenberg and Laufer (2017) came to interesting conclusions. Using the information on two million offers from the nine largest U.S. cities in the years 2008-2012, the authors showed that the asking price-based index accurately forecasts the Case-Shiller index (based on the repeat sales method and asking prices) with a few-month lead.…”
Section: Datamentioning
confidence: 89%
“…This reluctance by sellers to reduce prices during a market down-turn also implies that list-prices are not always good indicators of market turning points (Knight et al 1994). This asymmetry in list-price reaction to underlying market tendency probably explains why the literature provides a mixed verdict on whether list prices are good leading indicators for transaction prices: While some researchers find them to be good leading indicators (see e.g., Ahmed et al 2016;Anenberg and Laufer 2017;Lyons 2019) others find the opposite (Kolbe et al 2021).…”
Section: List-data Indicatorsmentioning
confidence: 99%
“…Survey data also tend to be backward-looking and suffer from participation biases because only some households/firms surveyed will respond. Finally, list prices from online platforms are typically higher than transaction prices, subject to revision over time, and often do not lead to actual transactions (Shimizu et al, 2016;Anenberg and Laufer 2017;Lyons 2019;Kolbe et al, 2021). lower prices (Deng and Liu 2009;Edelstein et al, 2012), choose the most attractive location, or make last-minute changes to floor plans.…”
Section: Introductionmentioning
confidence: 99%